The Promotion Mix Strategy of Craft Business: A Case Study In Naturalan.id - Dewi Nofitasari; Sandhya Parama Bramasthana; Alle Syafira Larasati; Tati Tri Lusi Yani (Institut Seni Indonesia Yogyakarta, 2023)
The rapid development of the arts and crafts business at this time has created intense competition among art and craft producers in Indonesia. Companies must compete to seize and dominate market share by providing the best service for consumers. Promotion strategy has an essential role in the success of a business. Without a promotional plan, consumers will not buy and even knowing the uses and advantages are one of the primary considerations for consumers to purchase a product. Naturalan.id is one of the well-developed arts and crafts businesses. To retain its customers, Naturalan.id carries out a promotional mix strategy that can increase sales. This research focuses on determining how Naturalan.id carries out the promotional system Kasongan Art Market in growing sales. The data collection used is utilizing observation, interviews, and documentation. The author uses a qualitative method with a case study approach to analyse the data. The results showed that Naturalan.id's promotional strategy was carried out by advertising, personal selling, sales promotion, and publicity. The strategy that has been carried out by Naturalan.id has been and is quite effective in developing and increasing sales and increasing the number of visitors.